The Influence of Salary and Work Environment in Human Resource Development on Work Productivity - Adiwima Zebua; Togu Harlen Lbn. Raja; Lasman Eddy Bachtiar; Sri Mei Cahaya Lestari Waruwu (Journal of Educational Management Research, 2025)
This study aims to analyze the effect of salary and work environment on employee work productivity. The research focuses on determining whether salary and work environment partially and simultaneously influence productivity and identifying the extent of their contributions. This quantitative research uses a causal associative approach, with a population of 61 employees selected through a census sampling technique. Data were collected using questionnaires, observations, and documentation, and analyzed through multiple linear regression, t-test, F-test, and the coefficient of determination (R²) using SPSS version 27. The results show that salary and work environment both have a positive and significant effect on employee productivity, demonstrated by the t-test results where salary (X1) and work environment (X2) significantly influence productivity (Y) with sig. < 0.05. The simultaneous F-test also indicates a significant effect, and the adjusted R² value of 0.509 shows that 50.9% of productivity is influenced by both variables. These findings imply the importance of fair compensation and conducive work conditions in improving employee performance and supporting strategic human resource management to increase organizational productivity.